Preparation of titania nanoparticles with tunable anisotropy and branched structures from core–shell molecular bottlebrushes. (19th August 2016) - Xie, Guojun; Ding, Hangjun; Daniel, William F.M.; Wang, Zongyu; Pietrasik, Joanna; Sheiko, Sergei S.; Matyjaszewski, Krzysztof
Abstract: Core–shell molecular bottlebrushes with various topologies and with poly ( tert -butyl acrylate)- b -polystyrene (P t BA- b -PS) block copolymer side chains were synthesized via atom transfer radical polymerization (ATRP). After hydrolysis of the P t BA segments and their conversion to poly (acrylic acid) (PAA), the materials were used as templates to prepare titania nanoparticles. Transmission electron microscopy (TEM) images showed that the particles retained the characteristic shape of the templates, including branches and cylindrical geometry. The cylindrical dimensions, i.e. diameter and length, were controlled by the number average degrees of polymerization of the PAA side-chain block and the polymethacrylate backbone, respectively. Thermogravimetric analysis (TGA) showed the weight fraction of inorganic content ranged from 17% to 35%, depending on the ratio of the length of PAA and PS blocks. Graphical abstract: Highlights: Molecular bottlebrushes with tunable topologies and anisotropy were synthesized. Titania nanoparticles were prepared using brush templates with core–shell structures. Characteristic shape of the templates were transferred into hybrid nanoparticles.